Modern Trends In Continuous Professional Development In the Nigerian Educational Sector - Soye, Asawo, Sotonye (International Journal on Integrated Education, 2023)
The COVID-19 pandemic brings with it disruptions in earlier established methods of undertaking task and rendering services, the educational sector in Nigeria being no exception. This disruption requires new methods for continuous professional development of teachers. This theoretical paper focused on the importance of new methods of continuous professional development of teaching staff in Nigeria’s school system in the face of the global challenges which affects the educational sector like every other sector. The importance of continuous professional development was underscored. Continuous Professional Development was viewed as a means where teaching professionals keep their knowledge and skills current so that they can deliver the high quality of service that safeguards the public and meets the expectations of customers (students), and the requirements of their profession. The paper reiterated the fact that the unanticipated challenges of the COVID -19, IDPs, etc. has put the teaching staff in the position of being relevant to offer professional services to whom, and where it is needed. The advantages of the technological age, aided by advances in Information and Communication can be taken advantage of, for teaching professionals to add to their knowledge current trends, alongside the traditional physical classroom instruction methods.